Anterior Loop of the Mental foramen in a Turkish Subpopulation with Dentate Patients: a Cone Beam Computed Tomography Study - NAMDAR PEKİNER, FİLİZ MEDİHA (AVES PRESS LTD, 2015)
Objective: The aim of this retrospective study was to evaluate the frequency and types of the mental foramen's anterior loop in a Turkish subpopulation on cone-beam computed tomography (CBCT). Methods: 279 dentate patients (138 females, 141 males, age range 20- 69 years) were evaluated for both side of mandible. Type 1 was described as the mental branch leaved the inferior alveolar nerve posterior to the opening of the mental foramen. Type 2 was described as the mental branch leaved the inferior alveolar nerve perpendicular to the opening of the mental foramen. Type 3 was described as the mental branch leaved the inferior alveolar nerve anterior to the mental foramen. It was assumed that there was no loop in type 1 and 2. Type 3 indicated the presence of anterior loop. Results: The distribution of type 3, type 2 and type 1 were noted 59.5%, 31.9% and 8.6% respectively. if the type was same on both sides distribution of type 1, type 2 and type 3 were noted 1.8%, 17.2% and 45.5% respectively. There was no statistically significant difference on the left side and right side between males and females. Conclusions: CBCT can be used safely to observe three-dimensionally the track of mental nerve from the inferior alveolar nerve to the mental foramen. Thus the divergence of mental nerve can be evaluated if there is a loop mesially from the mental foramen for various surgical operations involving interforaminal area.
Keywords: Cone beam computed tomography; mandibular canal; inferior alveolar nerve; mental foramen; anterior loop